Suddenly Online: How Russian Students Switched to Distance Learning During the COVID-19 Pandemic (Comparative & International Education Series, 2021)
Russian universities went fully online on one day of March 2020. Many classes began to be taught remotely, some of them were replaced by online courses or postponed till Fall 2020. These events significantly changed students’ life and learning experience. Based on a survey data from more than 18 000 students across the country, we revealed that the most common difficulties students face during distance learning are a poor internet connection, a lack of interactions with peers and faculty, insufficient self-regulated learning skills, and a lack of a convenient place to study at home. These problems are more common for students from families with low income, those who believe that distance learning is less effective than face-to-face and freshmen. However, a third of students preferred distance learning to face-to-face. The results show that the employed, computer science students, students believing in the effectiveness of online learning, experiencing fewer difficulties during distance learning, and students satisfied with the way their university arranged the distance format are more likely to prefer distance learning over face-to-face learning in the future.